If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x(x + 4) = 10x + -81 Reorder the terms: 25x(4 + x) = 10x + -81 (4 * 25x + x * 25x) = 10x + -81 (100x + 25x2) = 10x + -81 Reorder the terms: 100x + 25x2 = -81 + 10x Solving 100x + 25x2 = -81 + 10x Solving for variable 'x'. Reorder the terms: 81 + 100x + -10x + 25x2 = -81 + 10x + 81 + -10x Combine like terms: 100x + -10x = 90x 81 + 90x + 25x2 = -81 + 10x + 81 + -10x Reorder the terms: 81 + 90x + 25x2 = -81 + 81 + 10x + -10x Combine like terms: -81 + 81 = 0 81 + 90x + 25x2 = 0 + 10x + -10x 81 + 90x + 25x2 = 10x + -10x Combine like terms: 10x + -10x = 0 81 + 90x + 25x2 = 0 Factor a trinomial. (9 + 5x)(9 + 5x) = 0Subproblem 1
Set the factor '(9 + 5x)' equal to zero and attempt to solve: Simplifying 9 + 5x = 0 Solving 9 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 0 + -9 5x = 0 + -9 Combine like terms: 0 + -9 = -9 5x = -9 Divide each side by '5'. x = -1.8 Simplifying x = -1.8Subproblem 2
Set the factor '(9 + 5x)' equal to zero and attempt to solve: Simplifying 9 + 5x = 0 Solving 9 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 0 + -9 5x = 0 + -9 Combine like terms: 0 + -9 = -9 5x = -9 Divide each side by '5'. x = -1.8 Simplifying x = -1.8Solution
x = {-1.8, -1.8}
| 17b+3=-422 | | 18=18y-18 | | 3c+45=7.2-6c | | 7m^2-2m+2=0 | | 21=6m-9 | | -7+z/4=0 | | -7m^2+2m-2=0 | | (x-10)+(x+2)=90 | | 6x+(-3)=117 | | 4(y+7)-7y=37 | | 6s-27=-19+4s | | 8x-143=-127 | | 9n-26=9+4n | | 436x-789=-571 | | 23x^2-20=0 | | -13x+28=-11 | | Y^2-.6y+.1=0 | | Y^2-.6y+.1111111111=0 | | 6x+18=4x+2 | | 3b(4-2b)-6b=-b(6b+7)+104 | | 12x+(-18)=66 | | -5x+13=58 | | 2.1(3y+1)-1.8=1.7(7y-8)-2.9 | | 3x-5=2x-9 | | y=-12+6x | | -2x+6=2 | | 4x^4-36x^2+9=0 | | y=6x-12 | | 7y^2-y+3=0 | | x^4-8x^2+13=0 | | -3x-11=4 | | 3x-5=64 |